Mistakes in internal medical documentation handling - Susło, Robert; Trnka, Jakub; Drobnik, Jarosław; Mastalerz-Migas, Agnieszka (Przewodnik Lekarza/Guide for GPs, 2008)
Medical files are part of individual medical documentation. They serve mainly as a registry for data describing patients’ health and various medical procedures. The way they should be kept is described by various legal rules. A medical practitioner who aims to keep medical files properly not only needs to know the formal rules, but also must be aware of their various uses and the most common mistakes. There are many potential benefits, but also challenges, connected with the emerging possibility to keep medical files in digital form only, without using paper documents at all. The digital data features are a possible source of data security violation and new kinds of medical practitioners’ mistakes.